PENGARUH WORD OF MOUTH DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN PADA KOHWA COFFEE HOUSE DI PAMULANG TANGERANG SELATAN - Pangestu Citra Wijaya, Katterina; Inva Jaswita, Derizka (Journal of Research and Publication Innovation, 2024)
This study aims to determine and analyze the effect of Word of Mouth and Location on Purchasing Decisions at Kohwa Coffee House Pamulang South Tangerang both partially and simultaneously. The research method used is a descriptive quantitative approach. The data used is primary data in the form of questionnaires distributed. The sample of this study were buyers at Kohwa Coffee House as many as 99 respondents. The results showed that Word of Mouth has a positive and significant influence on Purchasing Decisions where the t value is obtained > t table or (9.851 > 1.985) and reinforced by the p value < Sig. 0.05 or (0.000 < 0.05).Location has a positive and significant influence on Purchasing Decisions where the t value is obtained > t table or (14.385 > 1.985). And reinforced by the p value < Sig. 0.05 or (0.000 < 0.05). Word of Mouth and Location have a positive and significant influence on Purchasing Decisions where the F value is obtained > F table or (122.324 > 3.090), this is also reinforced by the p value < Sig.0.05 or (0.000 < 0.05).